2020
DOI: 10.1016/j.techfore.2019.119876
|View full text |Cite
|
Sign up to set email alerts
|

Diaspora entrepreneurs’ push and pull institutional factors for investing in Africa: Insights from African returnees from the United Kingdom

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 104 publications
1
23
0
Order By: Relevance
“…These firms classify informal arrangements as the embodiment of social conventions for their trade activities (Boso et al, 2019;Daniel et al, 2018). They see them as symbolic of accepted norms, codes of ethics and personal networks, and they perceive them as representative of shared social values, attitudes and behaviours that shape economic relationships (George et al, 2016;Nyame-Asiamah et al, 2020). Oppong's ( 2019) study of 134 Ghanaian small exporting firms concluded that informal institutions are influencing the way (behaviour) exporting firms adopt when engaging in export trade.…”
Section: Informal Institutions and Export Behaviour In Developing Economiesmentioning
confidence: 99%
“…These firms classify informal arrangements as the embodiment of social conventions for their trade activities (Boso et al, 2019;Daniel et al, 2018). They see them as symbolic of accepted norms, codes of ethics and personal networks, and they perceive them as representative of shared social values, attitudes and behaviours that shape economic relationships (George et al, 2016;Nyame-Asiamah et al, 2020). Oppong's ( 2019) study of 134 Ghanaian small exporting firms concluded that informal institutions are influencing the way (behaviour) exporting firms adopt when engaging in export trade.…”
Section: Informal Institutions and Export Behaviour In Developing Economiesmentioning
confidence: 99%
“…For its part, Western markets can be attractive for investors from developing countries that is proved by the example of the behavior of entrepreneurs from African countries: desperate to overcome the weakness of the formal institutions of the national economy, they form generally successful business communities in Great Britain [16]. Researchers have obtained similar results using the example of Turkey: based on data for 2002-2016.…”
Section: Investment Potential Factors: Methodology Overviewmentioning
confidence: 91%
“…As entrepreneurs or investors often belong to diverse relationships networks and social groups (Hernández-Carrión et al , 2020), migrant entrepreneurs and investors are also encouraged to use their contacts and networks to influence government policies and legislature in favor of open access market for the development of diaspora entrepreneurship. Since diaspora entrepreneurs often rely on informal institutions and social networks to engage in entrepreneurial activities in their countries of origin (Nielsen and Riddle, 2007; Nyame-Asiamah et al , 2020; Rana and Elo, 2017), Haitian diaspora entrepreneurs could use the same strategy to bypass the constraints imposed by the weakness of the formal institutions in order to take advantage of numerous business opportunities. For effective institutional reforms and control of corruption to take place, diaspora entrepreneurs must transform themselves into agents of institutional change capable of rallying consensus to change the rules of the game and help break the cognitive, legal and political obstacles that prevent market-supporting institutions from emerging (see Kuchar, 2016).…”
Section: Discussionmentioning
confidence: 99%